Paradoxical Sleep Suppresses Immediate Early Gene Expression in the Rodent Suprachiasmatic Nuclei - Decker, Michael J.; Rye, David B.; Lee, Shih-Yu; Strohl, Kingman P. (Frontiers in Neurology, 2010)
Light stimulates neuronal activity with subsequent expression of the protein product of the immediate early gene, c-fos, in the Suprachiasmatic Nuclei (SCN). Non-photic stimuli is also thought to modulate activity within the SCN. Here, we sought to determine the effects intrinsic stimuli, specifically, the states of wakefulness and sleep upon c-fos protein expression in the SCN. In 16 rats, c-fos protein expression was evaluated at a fixed time of 1600 hours (subjective night), following one hour of electroencephalographically defined sleep. During sleep, as the state of paradoxical sleep (PS) increased, c-fos protein expression decreased (r -0.41, p < 0.033). The PS-associated reduction of c-fos positive cells occurred equally between animals asleep in the light and those asleep in the dark. We propose a model whereby PS duration might function as a homeostatic-entraining mechanism to reduce neuronal activity within the SCN, and thereby modulate circadian rhythms during sleep.